Comparative Analysis of Various Methods of Gingival Retraction in Orthodontics (Progress Annals: Journal of Progressive Research, 2023)
In modern orthodontic treatment, the display of the features of the formed tooth stump, especially the ledge line, is a prerequisite for high-quality restorations. We performed gingival retraction on 40 patients, ranging in age from 21 to 53 years, using traditional and modern methods. Retraction threads were used, whose impregnation included various chemical compounds and pastes for gingival retraction. Results were discussed in terms of the physicochemical properties of the means used, the quality of the impressions obtained, the atraumatic nature of the retraction, and its effect on the overall physical condition of the patient. Results were recorded using a multifunction laser diagnostic device "LAKK-M" and an electronic tonometer. The quality of the impressions was assessed visually. We conclude on the advantages and disadvantages of the systems used and their influence on the general dental condition of the patients